2022
DOI: 10.1038/s41467-022-32489-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for Sarbecovirus ORF6 mediated blockage of nucleocytoplasmic transport

Abstract: The emergence of heavily mutated SARS-CoV-2 variants of concern (VOCs) place the international community on high alert. In addition to numerous mutations that map in the spike protein of VOCs, expression of the viral accessory proteins ORF6 and ORF9b also elevate; both are potent interferon antagonists. Here, we present the crystal structures of Rae1-Nup98 in complex with the C-terminal tails (CTT) of SARS-CoV-2 and SARS-CoV ORF6 to 2.85 Å and 2.39 Å resolution, respectively. An invariant methionine (M) 58 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Interestingly, a single point mutation in ORF6 (ORF6 D61L ) recently emerged in the Omicron subvariants BA.2 and BA.4 that is no longer present in the now dominant BA.5 subvariant, which otherwise shares a lot of similarities with BA.4 ( 19 ). The ORF6 D61 residue is located in close proximity to the key M58 residue at the C-terminal tail (CTT) of the protein that directly binds to the RNA binding pocket of the Nup98-Rae1 complex ( 15, 28 ) and accompanying paper). Therefore, we sought to investigate the impact of this mutation on the ability of ORF6 to interact with the Nup98-Rae1 complex and inhibit IFN signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a single point mutation in ORF6 (ORF6 D61L ) recently emerged in the Omicron subvariants BA.2 and BA.4 that is no longer present in the now dominant BA.5 subvariant, which otherwise shares a lot of similarities with BA.4 ( 19 ). The ORF6 D61 residue is located in close proximity to the key M58 residue at the C-terminal tail (CTT) of the protein that directly binds to the RNA binding pocket of the Nup98-Rae1 complex ( 15, 28 ) and accompanying paper). Therefore, we sought to investigate the impact of this mutation on the ability of ORF6 to interact with the Nup98-Rae1 complex and inhibit IFN signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Since NXF1-NXT1 interacts with phenylalanine-glycine (FG) repeats on nucleoporins, such as Nup98, to mediate docking of messenger ribonucleoproteins (mRNPs) and facilitate trafficking trough the NPC ( 39, 40 ), we hypothesized that ORF6 could also interfere with this process. In addition, structural data have recently shown that, similarly to VSV M and herpesvirus ORF10 proteins ( 37, 38 ), the CTT of ORF6 directly interacts with the RNA binding groove of the Nup98-Rae1 complex and competes for in vitro binding of single-stranded RNA ( 15, 28 ). Consistent with these notions, our results show that ORF6 expression can indeed block Nup98-Rae1 mRNA export functions and this contributes to the shutoff in protein synthesis that occurs during SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…To date, structural information on ORF6 protein has been limited to its existence as a complex comprising a C-terminal tail, Rae1, and Nup98. , According to our earlier study, ORF6 protein existed either in clusters or in large aggregates, localized in the perinuclear region rather than confined in the nuclear rim. Using counterstaining, Wong et al demonstrated that ORF6 protein resides on the endoplasmic reticulum (ER), Golgi apparatus, and mitochondria. We hypothesize that ORF6 protein could aggregate and form a shield at the perinuclear region to trap host nucleoporins (Rae1 and Nup98) or sequester nuclear transport receptors (karyopherins α). , This hypothesis could explain the cytoplasmic retention of nucleoporins and impaired nuclear import in ORF6-expressing cells. Moreover, a similar mechanism has been reported for SARS-CoV ORF6 protein .…”
mentioning
confidence: 75%
“…To date, structural information on ORF6 protein has been limited to its existence as a complex comprising a C-terminal tail, Rae1, and Nup98. 12,13 According to our earlier study, ORF6 protein existed either in clusters or in large aggregates, localized in the perinuclear region rather than confined in the nuclear rim. 5 Using counterstaining, Wong et al demonstrated that ORF6 protein resides on the endoplasmic reticulum (ER), Golgi apparatus, and mitochondria.…”
mentioning
confidence: 90%
See 1 more Smart Citation